The Dutchman, Chinese Klonthong, Javanese Skippers in Trade on the North Coast of Java in the 18th Century - Ahmad Fauzan Baihaqi; Rizkinta Sembiring Meilala, Bryna; Fithor, Alin (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
ABSTRACT This paper discusses the differential social structure activities of Dutch Businessmen or VOC, Chinese Klontong and Javanese Shipowners. After the disintegration of the Mataram Kingdom in the 18th century, it had an impact on the economic activities of the middle class of non-European traders on the North Coast of Java. The decline of the maritime trade situation in the 17th century in Southeast Asia in general and in Java in particular was caused by the VOC's military economic monopoly intervention pattern and agrarian kingdoms that did not pay attention to trade shipping. This writing uses a qualitative method with a socio-historical approach. This writing uses Mahan's theory that a strong maritime state must have a strong navy. This can be seen how the VOC maximized the military potential of its navy in dominating trade shipping on the North Coast of Java. Since then Java has been characterized by a rejection of the weak merchant class. The king of Java's choice to pull the economic center to the south also influenced the VOC's trade dominance on Java's North Coast. However, the economic pressure of the VOC slowly led to the emergence of a middle class that came from outside the rule of the royal class. This middle class was filled by Madurese captains alongside Javanese Nahkoda, as well as Chinese merchants, for the latter were considered tenacious despite often having strong trade relations with the Dutch or the VOC marking the discourse on the dynamics of trade and shipping in port cities on the North Coast of Java. Keywords: VOC, Chinese Klonthong and Java Skipper, Shipping and Trade